Improving Learning Outcomes in Rhythmic Movement Activities at Pusakajaya Utara II Elementary School - Resita, Citra; Saepudin (ILIN Education Indonesia, 2023)
The background of the problem of this learning comes from the way the teacher learns and the way students learn, causing the low learning outcomes of students in PJOK learning to be seen that the teacher has not been able to arrange students' activities from easy to difficult. Learners have not been able to master the material when the assessment takes place. And this study aims to determine the basic movement skills (hand swings and footsteps) in learning rhythmic activity activities.This research uses Classroom Action Research (PTK). The subjects in this study were class IV (four) students of Pusakajaya Utara II State Elementary School, totaling 30 students. Data collection is done by selecting data sources, types of data, and instruments used in research. The results of this study can be concluded that: Through learning Rhythmic Movement activities can improve basic movements in class IV students of Pusakajaya Utara II State Elementary School. The increase in ability is seen from the achievement of the Minimum Completion Criteria (KKM) of students classically in the pre-cycle of 32.14%, cycle I is 64,29%, and cycle II reaches 89,29%. Based on the results of the final test, there has been an increase, so it can be concluded that the ability of basic movements can be improved through rhythmic gymnastics for class IV students of Pusakajaya Utara II State Elementary School.